Molodezh'! Voz'mi nad prirodoy shefstvo! - Rudkovich, A (Плакат СССР (Plakat), 1977)
Young female Soviet soldier in front of photomontage of forest wildlife Original title: Молодежь! Возьми над природой шефство! PO-1150